Prefabricated resin veneer: A case report of a simplified restorative technique - Pedro Paulo Albuquerque; Marina Barreto Pereira Moreno; Alexander Cassandri Nishida; Ezequias Rodrigues; Camila Kiyohara; Carlos Eduardo Francci (Tabriz University of Medical Sciences, 2018)
Background. The aim of this study was to describe the step-by-step procedures of clinical cases using prefabricated composite resin veneers (PCRVs), manufactured with the Brilliant New Generation composite resin (Coltene, Altstätten, Switzerland). Direct composite veneers presented some drawbacks such as the difficulty of execution and color instability of the composite resin over time. The simplified application of the PCRVs has been introduced as an interesting alternative in cases of smile asymmetry, large deficient restorations and discolored teeth. In the present investigation, the PCRV technique is described completely to help the dentist during the planning and execution of treatments with the Componeer system. Conclusion The treatment with Componeer Brilliant NG yielded excellent aesthetic results. PCRV technique is simpler than direct composite veneer technique. The specific characteristics of the system can promote the results with greater aesthetic longevity. It is important to highlight that this procedure does not replace the already established veneer technique with dental ceramics. Clinical implication. PCRVs yielded excellent surface gloss. Their dimensions, based on the golden ratio, facilitates the technique and is an excellent alternative in the aesthetic restorative treatment in the anterior region.